Support for Parents of Children with Learning Difficulties: Foundations for Child Success - Shakhnoza Khaydarova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Parental support is a cornerstone for the academic, emotional, and social development of children with learning difficulties. Research shows that when parents receive targeted interventions—ranging from psychoeducational programs to cognitive based therapies—they experience reduced stress, enhanced coping skills, and stronger parent–child relationships, which in turn translate into improved student outcomes. This article reviews current evidence on intervention strategies, ethical considerations, and regulatory frameworks, and offers best practices for practitioners and policymakers aiming to bolster family-centered support in special education.